Identifying the Patterns of Orthopaedic Trauma During the Victorian COVID-19 Lockdowns: An Interrupted Time Series Study - Lucas R. Neumaier; Joanna F. Dipnall; Susan Liew; Belinda J. Gabbe (Trauma Care, 2025)
Objectives: this study aimed to compare the admission volume and characteristics of patients with traumatic orthopaedic injuries before, during, between, and after the COVID-19 lockdowns in metropolitan Victoria, Australia. Methods: A multi-centre, registry-based cohort study with an interrupted time series analysis was conducted using data from the Victorian Orthopaedic Trauma Outcomes Registry (VOTOR) for patients with a date of injury from January 2017 to June 2022. Weekly admission volume, injury event characteristics, and in-hospital outcomes were analysed before, during, between, and after the two periods of COVID-19 lockdowns in metropolitan Melbourne (i.e., five periods). Results: During the first week of lockdown in Victoria (L1), the number of weekly orthopaedic trauma admissions declined by 24% relative to the preceding week, IRR 0.76 (95%CI 0.67, 0.87). However, the volume of admissions during the subsequent lockdown (L2) approximated pre-COVID levels. An immediate increase in orthopaedic trauma admissions occurred during the intermission (time between lockdowns) and post-COVID periods by 33% and 20%, respectively, compared to the preceding week. During periods of lockdown, patients were older (61 versus 58 years old), and a higher proportion were injured at home (38% versus 28%); fewer due to motor vehicle collisions (8% versus 11%). The pattern of injury by intent, body region injured, injury severity, and in-hospital mortality were unchanged. Conclusions: the impact of COVID-19 lockdowns on the volume and characteristics of hospitalised orthopaedic trauma was not uniform across consecutive lockdowns, but favoured injuries that occurred at home.